The bilateral effects of digital economy on regional carbon emissions in China - Liu, Chao; Wang, Wei; Ding, Chenhui; Teng, Xianzhong; Ye, Yuxin; Zhang, Zejing (Frontiers in Environmental Science, 2023)
The impacts of the digital economy on regional carbon emissions hashave attracted much concerns from all regions of China. Using panel data for 30 Chinese provinces and cities from 2011 to 2020, the study empirically examined the bilateral effects of the digital economy on regional carbon emissions (RCBs) and the heterogeneous characteristics under different conditions by various econometric models. The results indicate that the inhibition effect of digital economy development on regional carbon emissions is stronger than the promotion effect, which is 13.38% and 12.11% lower and higher than the frontier level respectively. When both effects are combined, it makes regional carbon emissions 1.27% below the frontier boundary, which means the digital economy significantly inhibits the increase of regional carbon emissions. And in terms of spatial and temporal distribution, the inhibition effect of the digital economy on carbon emissions (DECEs) predominant and presents a declining trend during the study period. However, the inhibition effect of the digital economy on carbon emissions inemissions in the eastern region is highest among all the regions. In addition, the level of different factors such as digitalas digital economy, human capital and economic development, can effectively strengthen the inhibition effect of digital economy on regional carbon emissions. Therefore, policy implications are proposed including facilating promoting construction and regulations for digital economy, implementing heterogeneous policies and strategies, and improving talent and economic development environment, to enhance the inhibition effect of the digital economy on China's regional carbon emissions.